Erratum: Xie, Z.-J.; Bao, X.-Y.; Peng, C.-F. Highly Sensitive and Selective Colorimetric Detection of Methylmercury Based on DNA-Functionalized Gold Nanoparticles. Sensors 2018, 18, 2679. - Zheng-Jun Xie; Xian-Yu Bao; Chi-Fang Peng (Sensors, 2018)
The authors wish to make the following corrections to their paper [...]